New generalised divergence measure for increasing functions. (2016) - Jain, K.C.; Chhabra, Praphull
New generalised divergence measure for monotonically increasing functions is proposed and properties, bounds, some relations are derived. Further, new divergence measure of this new generalised measure's class is introduced as well with properties, bounds and numerical verification.